Lectures on Innovation in Building Technology - Lecture Articles for Students of Architecture Delft 1992-2015 | Nottingham 2005-2011 - M. Eekhout (IOS Press, 2016)
This book is a collection of articles written in recent years and used in lectures for students at the Faculty of Architecture at Delft and at Nottingham University. The lectures and articles are based on a mixture of innovations in academia and industry. They elucidate the relationship between architecture and building technology, as well as high technology, transfer of technology, innovative design, development and research in the Chair of Product Development at TU Delft. With his experience in both industry and academia, Eekhout's goal is to bridge the gap between the two worlds and to stimulate them both, to prepare students to be inventive, innovative and daring enough to materialize their own dreams in practice. The lecture articles are based on the adventures and experiences in Mick Eekhout's design & build experimental laboratory cum factory, which works on projects all over the world, and for many interesting clients. Eekhout was able to develop an innovative technical vocabulary for lightweight structures and claddings in architecture and encourages students to attempt the same.